Unlocking Langkawi's tourism potential: Spatial analysis of attractions and facilities - Azizul, Ahmad; Ardiansyah, Ardiansyah; Nur Afiqah, Ariffin; Yaniza Shaira, Zakaria; Mohd Zulhafiz, Said; Norizawati, Mohd Ayob; Muhammad Isa, Abdullah; Lindah Roziani, Jamru; Asykal Syakinah, Mohd Ali; Norita, Jubit; Ryoji, Soda; Yoshinari, Kimura; et al. (UKM Press, 2026)
In Langkawi, tourism development has concentrated unevenly, resulting in spatial imbalances and infrastructure strain in major hubs like Kuah and Pantai Cenang. This study analyzes spatial patterns of tourism facilities to inform sustainable and equitable development. 244 points of interest (POIs) were compiled from brochures and websites and validated using GPS surveys, then categorized into Attractions (45), Accommodations (85), Shopping & Dining (55), and Facilities (59). Spatial analyses including Average Nearest Neighbor (ANN), Kernel Density Estimation (KDE) and Moran’s I were applied. The results reveal significant clustering of combined facilities (ANN = 0.43, p < 0.001), with high densities in Kuah and Pantai Cenang. In contrast, attractions show modest clustering (NNI ≈ 0.83, p ≈ 0.031) and slight dispersion (Moran’s I = –0.31, p ≈ 0.047). These patterns highlight concentration of tourism infrastructure in coastal hubs and relative paucity in the island’s interior. The findings underscore the need for infrastructure dispersal and risk mitigation strategies to avoid overdevelopment and ecological degradation. By applying spatial analytics to Langkawi’s tourism landscape, this work fills a scholarly gap and provides guidance for sustainable spatial planning in a vulnerable island context.